Stimulating Aerobic Energy Supply Reactions of Athletes in Rugby Union - Oleh Kvasnytsya; Valeria Tyshchenko; Ivan Hlukhov; Kateryna Drobot; Vita Khimich; Oleksandr Mozoliuk; Iryna Skrypchenko (OVS LLC, 2024)
Objectives. The study purpose was to evaluate the effectiveness of an experimental program of training means aimed at stimulating reactions of aerobic energy supply of athletes who are part of Ukraine national rugby union team. Material and methods. The athletes of the Ukrainian national rugby union team were divided into two homogeneous groups (experimental and control) consisting of 15 individuals. The experimental group underwent a specialized program aimed at developing aerobic energy supply, whereas the control group followed a standard training program. The object of study focused on the training process of Ukraine national rugby union team. Results. The results of testing rugby players in the experimental group demonstrated reliable changes in reactions of aerobic energy supply under the influence of a program of special training sessions. The most significant alterations were noted in the indicators of kinetics and stability of reactions. The indicators of O2 consumption and pulmonary ventilation in the intensity zone of anaerobic metabolism threshold increased significantly. There was a tendency to increase indicators characterizing the power of the respiratory response (max VE), in particular under conditions of growing fatigue (% excess VE). However, there were no significant changes in indicators of aerobic capacities components in the athletes' control group. Conclusions. We believe that the mentioned indicators mostly reflect specialized manifestations of rugby players' aerobic capacities and impact the increase of athletes' special functional capabilities.  This has been confirmed by the results of the analysis of urgent adaptive responses registered in model conditions of competition activity. As a result of the implementation of the specified experimental programme during the preparation process, the Ukrainian national team achieved 2nd place at the European Rugby Union Championship in the Trophy division of the 2022-2023 season.